Construçao de pilhas elétricas simples - Um experimento integrado de química e física - De Oliveira, Luiz Antonio Andrade [UNESP]; Valle, Gisele Gomes; Zanluqui, Luis André (My University, 2001)
In this article are described simple and inexpensive ways of assembling galvanic cells, using zinc, magnesium and copper plates directly immersed in electrolytic solutions. Citric fruit juices, or even tap water, can be used as electrolytic solutions. Voltage and current produced by the electrochemical cells are enough for running electrical devices with small power demand, such as analogical and digital clocks. The experiments can be explored as simple demonstrations of transformation of chemical into electrical energy for elementary school students, or as interdisciplinary experiments of Physics and Chemistry for more advanced students.
Keywords: Current; Electrochemical cell; Power; Voltage